Organisations de travail et développement durable : l’initiative des partenaires sociaux (organisations syndicales et paronales) de la Martinique - Danielle Laport (Études Caribéennes)
In the French West Indies, reflections on the concept of sustainable development are mainly oriented to the protection of the environment. In Martinique, the challenge of initiating sustainable development was first proposed by a politician, and a leader of an ecological association; this approach has been reinforced by the General Council of Martinique as part of AGENDA 21, which puts strong emphasis on the issue of natural risks and biodiversity. This approach to the environment is now backed by trade unions and employer organizations that serve within the Regional Association for the Improvement of Working Conditions. This approach aims to make the social dimension in the dynamics of sustainable development more evident in Martinique. La quête du sens